2011
DOI: 10.1007/s11270-011-0911-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of Magnetic Methods to Monitor Vertical Migration of Metal Pollutants in Soil

Abstract: In order to assess the use of magnetic methods to study vertical migration behavior of metal pollutants in natural soils, a controlled experiment was performed near Belle River, Ontario, Canada. The soil at the site consists primarily of clay-rich glacial till overlain by localized alluvium. Twenty PVC tubes (16″×8″) were inserted vertically into the ground as test capsules. Magnetite powder (<5 μm) was distributed on the surface of the soil inside ten tubes (10 grams/tube) to simulate anthropogenic contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In spite of the fact that the depth of the upper (anthropogenic) maxima in the soil profile is rather related to profile development, soil type, thickness of organic horizon etc. however certain migration of magnetic particles over the years between O and Ah horizons is not excluded (Sapkota and Cioppa, 2012;Dlouha et al, 2013).…”
Section: Vertical Changesmentioning
confidence: 99%
“…In spite of the fact that the depth of the upper (anthropogenic) maxima in the soil profile is rather related to profile development, soil type, thickness of organic horizon etc. however certain migration of magnetic particles over the years between O and Ah horizons is not excluded (Sapkota and Cioppa, 2012;Dlouha et al, 2013).…”
Section: Vertical Changesmentioning
confidence: 99%
“…The change in groundwater pressure affects the low-pressure area under the overburden and has different effects on various layers [28]. Due to the complexity of mechanical properties under different stratum conditions, the impact of subsidence on the movement of pollutants in different strata is different [29]. HS-GCMS analysis indicated that benzene content decreased significantly with the increase in soil depth [30].…”
Section: Introductionmentioning
confidence: 99%